PP.02.31: EFFECT OF OMEGA-3 ENRICHED FOOD ON OXIDATIVE STRESS LEVELS IN YOUNG HEALTHY MEN. (June 2015) - Rasic, L.; Cosic, A.; Kralik, Z.; Kralik, G.; Cavka, A.; Drenjancevic, I.
Abstract : Objective: Many studies have shown effect of omega-3 fatty acid pills on lipid profile, but there are no or quite few studies showing the effect of everyday food enriched with omega-3 fatty acids on lipid profile and other cardiovascular risk factors. This study aimed to determine the effect of omega-3 enriched food consumation on oxidative stress in young healthy men. Design and method: 20 young healthy men (age 20.8 ± 1.2) were recruited and included in protocol. Protocol consisted of 3 weeks of consuming chicken eggs, 3 eggs per day. 10 men in omega group (OG) consumed omega-3 enriched chicken eggs (omega-3 content 155, 72 mg per egg), and 10 men in control group (CG) consumed regular chicken eggs. Chicken omega eggs were produced by changing the diet of laying hens. Data collection was performed on the first and last day of the protocol. Oxidative stress was asessed measuring lipid peroxidation. Lipid peroxidation was measured by TBARS method (Thiobarbituric Acid Reactive Substances) in the collected blood samples. The study protocol and procedures conformed to the standards set by the latest revision of the Declaration of Helsinki and were approved by the Ethical Committee of the Faculty of Medicine, University of Osijek. Statistical analysis was performed using Wilcoxon Signed Rank test, P < 0.05 (SigmaPlot v11.2, Systat Software, Chicago, USA). Results: The results have shown statistically significant decrease in lipid peroxidation in OG after protocol compared to the values before protocol (TBARS, OG before protocol 0.051 ± 0.02 vs. after protocol 0.54 ± 0.03). No significant changes were detected in CG after protocol (TBARS, CG before protocol 0.051 ± 0.05 vs. after protocol 0.49 ± 0.1). Conclusions: This study showed the improving effect of omega-3 enriched food on the lipid peroxidation, which leads to the reduction of the levels of oxidative stress in young healthy population. This may be important indicator of the role of omega-3 enriched food in cardiovascular prevention.